PENGARUH LATIHAN LOMPAT TALI DENGAN PERLAHAN TERHADAP DAYA TAHAN PADA TIM PUTRA TENIS MEJA SMA NEGERI OLAHRAGA PROV.RIAU - Trilis Jondri; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based the results of observations conducted by researchers in the field, the researchers found that the problem is still the lack endurance on male team table tennis at sma olahraga riau province. Based on the existing problems, the researchers aim to provide a form of exercise that can increase endurance and exercise intensive program. In this study the researchers only focus on one form of exercise that exercises jump rope slowly for this exercise has never been applied for male team table tennis at sma olahraga riau province. This study used an experimental method, in order to determine the effect of exercise. This the experimental research method can be interpreted as the research methods used to find a specific treatment effect against the other in uncontrolled conditions. The first step taken is to Pree-test is a multistage fitness test. To measure the endurance of the ateletes before training. Subsequently the samples were treated namely practice jump rope slowly. Then do the final test is the post-test with the multistage fitness test, to see if there is increased after a given treatment. Data were analyzed descriptively, then further testing research hypotheses have been proposed to fit the problem is: there is influence of exercises jump rope significantly to the results of endurance. Based on t test analysis produces Tcount of 2,853 and Ttable of 2,353. Means that Tcount> Ttable. It can be concluded that H0 rejected Ha accepted. So it can be summed up as follows: there is a jump rope slowly exercise effect to endurance on male team table tennis at sma olahraga riau province.Keyword : Exercise jump rope slowly,Endurance